Treatment Outcomes of Re-irradiation in Locoregionally Recurrent Rectal Cancer and Clinical Significance of Proper Patient Selection - Chung, Seung Yeun; Koom, Woong Sub; Keum, Ki Chang; Chang, Jee Suk; Shin, Sang Joon; Ahn, Joong Bae; Min, Byung Soh; Lee, Kang Young; Kim, Nam Kyu; Yoon, Hong In (Frontiers in Oncology, 2019)
Background and purpose: Majority of patients with locoregionally recurrent rectal cancer will require re-irradation (reRT). This study aimed to analyze the treatment outcomes, particularly infield progression, and severe late toxicity rates after reRT for recurrent rectal cancer and further identify a subgroup of patients who may optimally benefit from reRT. Materials and methods: Patients with rectal cancer who underwent reRT to the pelvis between January 2000 and December 2017 were included for analysis. Results: The records of 41 patients were retrospectively reviewed. The median follow-up period after reRT was 53.7 months (range, 3.5-130.3 months). The 2-year infield progression-free rate (IPFR) was 49.4%. The 2-year overall survival (OS) and progression-free survival (PFS) rates were 55.3% and 28.5%, respectively. Severe late toxicity events occurred in 17 patients, and the median time from reRT to severe late toxicity event was 10.5 months (range, 2.3-33.3 months). The 2-year severe late toxicity free-rate (SLTFR) was 55.5%, and the median SLTFR was 33.3 months. Patients who did not experience severe late toxicity events showed a significantly higher number of recurred tumors at the posterior or lateral location compared to axial or anterior location. The selected subgroup with recurrent tumor size <3.3 cm and treated with total reRT dose of >50 Gyab10 (n=13) showed superior IPFR, OS, and PFS to the other patients. Conclusion: ReRT was a reasonable treatment option for patients with locoregionally recurrent rectal cancer. However, severe late toxicity rates were substantially high. Thus, patients indicated for ReRT with curative dose should be selected properly according to tumor size and location.